Analysis of indigenous community conflicts on illegal mining in Botak mountain of Buru district - Laode Alimin (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
The results of the study by the authors of the analysis that there are found 4 factors that influence the occurrence of conflict in the area of Buru Regency mountain gold mining bald. First, there is a struggle for mining land between indigenous peoples. Secondly, indigenous peoples claim land ownership over their customary rights. third, Conflict Policy from the government towards the closure of Mining in the bald mountain area. Of the 3 factors, this is the stage in the problem in the bald mountain until the conflict from the real gold mining is found open until now. The instructions from the Buru Regency Regent followed up by issuing the Regent Instruction Number 1 of 2012 concerning the handling of social disasters as a result of the management of illegal gold mining on Mount Bald in Buru Regency. In this case, in order to follow up on the policy, the two Instructions by the Regional Government agencies along with the Security Apparatus from the TNI and POLRI conducted sweeping in the illegal gold mining area on bald mountain.